2020
DOI: 10.1111/sms.13899
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness attenuates the genetic predisposition to obesity in children and adolescents

Abstract: Obesity is an important risk factor associated with non‐communicable cardiometabolic diseases. Previous studies have indicated that children and adolescents with a predisposed genetic risk for obesity could benefit from an active lifestyle, but there are no studies investigating whether physical fitness moderates the association of genetics and obesity. The aim of this study was to verify the moderating role of physical fitness in the relationship between genetic risk score (GRS) and body mass index (BMI) in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Cytokines and hormones (i.e., CRP, IL-6, Leptin) play a relevant role in brain functioning; hence paediatric obesity would affect brain structure and function ( 58 , 60 ). However, it has been shown that physical fitness counteracts the effect of obesity meditating on various physiopathological processes, for instance, inducing an anti-inflammatory mechanism at the organic level ( 61 ), and also attenuating the genetic predisposition to obesity in children and adolescents ( 62 , 63 ). A study in children and adolescents with overweight and obesity showed that CRF and S-AF were associated with several cortical and subcortical brain structures, even after controlling for BMI and other covariates ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines and hormones (i.e., CRP, IL-6, Leptin) play a relevant role in brain functioning; hence paediatric obesity would affect brain structure and function ( 58 , 60 ). However, it has been shown that physical fitness counteracts the effect of obesity meditating on various physiopathological processes, for instance, inducing an anti-inflammatory mechanism at the organic level ( 61 ), and also attenuating the genetic predisposition to obesity in children and adolescents ( 62 , 63 ). A study in children and adolescents with overweight and obesity showed that CRF and S-AF were associated with several cortical and subcortical brain structures, even after controlling for BMI and other covariates ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…The quantity and quality of DNA were assessed by using the NanoDrop spectrophotometer (NanoDrop ™ One/OneC Microvolume UV-Vis Spectrophotometer; Thermo Fisher Scientific) and tested on Perrone et al Journal of Translational Medicine (2022) 20:107 agarose gel. NGS analysis was carried out using a targeted panel including genes and polymorphisms (see Additional file 1: Table S1), [16][17][18][19][20][21][22][23][24][25][26][27][28][29] related to diet, lifestyle, and physical performance/sports, on the Ion Gene Studio S5 platform (Thermo Fisher Scientific). The genes and specific SNPs were chosen for sequencing based on their significant biological roles in the lipid metabolic pathways and/or correlation with bioclinical parameters.…”
Section: Genotypingmentioning
confidence: 99%
“…While it is true that there are many studies analyzing fitness associated with health [ 24 , 39 , 40 , 41 ], few studies have investigated the association between the fitness level and the LBP [ 42 , 43 , 44 ], especially in child populations [ 45 , 46 , 47 ]. In the present study, higher levels of PA were associated with the absence of LBP.…”
Section: Discussionmentioning
confidence: 99%